The Performance of SISO in Wireless Open-access Research Platform (WARP) Using QAM Modulation - Jenny Putri Hapsari; Ida Anisah (IAES Indonesia Section, 2016)
This paper shows the implementation of SISO communication system using QAM modulation in WARP. The performance of the proposed system is evaluated in terms of BitError-Rate (BER) for different M-array level: 4, 8, and 16 in indoor and outdoor environments, both using LOS condition. In the analysis results, SISO performance with 4-QAM modulation achieves better performance compared to 8-QAM and 16-QAM for both environments. Meanwhile, SISO performance with QAM modulation in outdoor environment achieves better results compared to indoor environment for different M-array level. In indoor environment with transmitted power -26 dBm, BER achieved for 4-QAM, 8-QAM, and 16-QAM are 1.33 × 10−4, 2.078 × 10−2, and 8.76 × 10−2, respectively. While in outdoor environment with the same transmitted power, BER achieved for 4-QAM, 8-QAM, and 16-QAM are 0, 1.497 × 10−2 and 5.928 × 10−2, respectively. SISO performance using M-QAM modulation is better than using M-PSK modulation